Hank The Cowdog: The Case of the Haystack Kitties - Book 30 - Erickson, John R. (Houston TX, 1998)
Summary: Hank the Cowdog's adventures include being trapped in a runaway pickup truck and later discovering a nest of trespassing stray cats in a haystack.
Keywords: Dogs; Fiction